Celastrol attenuates sodium oxalate-induced acute kidney injury and crystal deposition by inhibiting NF-κB - LIU Yiheng; LIU Yiheng; ZHENG Quanyou; ZHANG Wanyuan (陆军军医大学学报)
Objective‍　‍To investigate the role and possible mechanism of celastrol (Cel) in sodium oxalate (NaOx)-induced acute kidney injury (AKI) and crystal deposition in the kidney tissues in mice. Methods‍　‍Male C57BL/6 mice (aged 8~12 weeks, weighing 22~24 g) were randomly divided into 3 groups. Saline group (control group, intraperitoneal injection with normal saline and drinking water freely), NaOx group (injured group, intraperitoneal injection of 75 mg/kg NaOx, and drinking water containing 50 μmol/L NaOx), and NaOx+Cel group (treatment group, intraperitoneal injection of 1 mg/kg Cel firstly and then 75 mg/kg NaOx in 24 h later, drinking water containing 50 μmol/L NaOx). All specimens were collected in 24 h after NaOx injection. HK-2 cells were randomly divided into 4 groups: Medium group (no treatment), NaOx group (500 μmol/L NaOx), NaOx+Cel group (400 nmol/L Cel pre-treatment for 2 h followed by 500 μmol/L NaOx treatment), and NaOx+Cel+BA group [8 μmol/L betulinic acid (BA, NF-κB agonist) after the interventions as the NaOx+Cel group]. Cells of each group were collected in 24 h after corresponding treatments. Von Koosa and cell adhesion assays were used to observe crystal deposition. HE staining was employed to observe renal histopathology and score the damage. CCK-8 assay was utilized to detect cell viability to obtain the optimal concentrations of NaOx and Cel. Serum urea and creatinine levels were detected. Immunohisotochemical assay was conducted to detect the expression of OPN, CD44, KIM-1, NGAL, p65, IL-1β, BAX, and Caspase-3, and Western blotting was performed for protein levels of OPN, CD44, KIM-1, p65, P-p65 and IL-1β. Results‍　‍The mice in the NaOx+Cel group showed reduced crystal deposition (P<0.0001), attenuated renal tubular damage (P<0.01), decreased serum urea and creatinine levels (P<0.05), and declined expression levels of the renal adhesion molecules OPN and CD44, the kidney injury molecules KIM-1 and NGAL, the inflammation-associated molecules p65 and IL-1β, and the apoptosis related molecules BAX and Caspase-3 when compared with the NaOx group (P<0.05). In in vitro study, the NaOx+Cel group showed reduced crystal adhesion (P<0.0001), decreased expression of the adhesion molecules OPN and CD44 (P<0.05), down-regulation of the inflammatory molecule IL-1β and P-p65/p65 ratio (P<0.05), and down-regulation of the renal injury molecule KIM-1 (P<0.05) when compared with the NaOx group. In the NaOx+Cel+BA group, crystal adhesion was significantly increased (P<0.0001), the inflammatory molecule IL-1β and the ratio of P-p65/p65 were increased (P<0.05), and the kidney injury molecule KIM-1 was increased when compared with the NaOx+Cel group (P<0.05). Conclusion‍　‍Cel may reduce NaOx-induced crystal deposition and AKI by inhibiting NF-κB activation.